Structure of Dairy Products. - Tamime, Dr. Adnan (Society of Dairy Technology series., 2007)
Structure of Dairy Products. SOCIETY OF DAIRY TECHNOLOGY SERIES. Edited by A.Y. Tamime. The Society of Dairy Technology (SDT) has joined with Blackwell Publishing to produce a series of technical dairy-related handbooks providing an invaluable resource for all those involved in the dairy industry; from practitioners to technologists working in both traditional and modern large-scale dairy operations. The previous 30 years have witnessed great interest in the microstructure of dairy products, which has a vital bearing on, e.g. texture, sensory qualities, shelf life and packaging requirements o.